Bunching and non-bunching at kink points of the Swedish tax schedule - Spencer Bastani; Håkan Selin (Center for Economic Studies and ifo Institute (CESifo), 2012)
Recent microeconometric studies of taxpayer' responsiveness to taxation have shown that intensive margin labor supply and earnings elasticities typically are modest and sometimes equal to zero. However, a common view is that long-run responses might still be large since micro-estimates are downward biased owing to optimization frictions. In this paper we estimate the taxable income elasticity at a very large kink point of the Swedish tax schedule using the bunching method. During the period of study the change in the log net-of-tax rate reached a maximum value of 45.6%. Interestingly, we obtain a precise elasticity estimate of zero for wage earners at this large kink. The size of the kink allows us to derive tighter bounds on the long-run elasticity than previous studies. If wage earners on average tolerate 1% of their disposable income in optimization costs, the upper bound on the long-run taxable income elasticity is 0.39. We also evaluate the performance of the bunching estimator by performing Monte Carlo simulations.
Keywords: H21; H24; J22; 330; bunching; taxable income; bounds; optimization frictions; Einkommensteuer; Steuerwirkung; Arbeitsangebot; Einkommenselastizität; Optimale Besteuerung; Schätzung; Schweden